PENGARUH PEMBELAJARAN BERBASIS WEBSITE TERHADAP HASIL BELAJAR SISWA - Muhammad Yunus; M Riski Ardiansyah; Jufri Jufri; Adyanata Adyanata; Agung Setiawan; Rina Wati Rina (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
This study aims to determine the effect of web-based learning on student learning outcomes. Learning outcomes are the achievement of student development standards to participate in learning activities over a certain period of time. Learning outcomes can measure students' ability to set learning objectives. This research was conducted at SMKN 2 Rambah using a website-based learning model. The purpose of this research is to reveal and analyze the learning process using the website. The method used in this study is the method by collecting data to answer questions using a qualitative research approach. The targets in this study were 20 TKJ students. The results of the study show that website-based learning has less effect on student learning outcomes. During learning students are effective in learning and students understand the material displayed. The results of the study show that the website-based learning process is effective in improving student learning outcomes